Chucky. Season two [videorecording (DVD)] - Mancini, Don, 1963- (Universal, 2023)
Chucky is back! The notorious killer doll continues his onslaught of terror in Season Two of the hit horror series from franchise creator Don Mancini. This season finds Chucky hellbent on exacting revenge against teens Jake, Devon, and Lexy, as well as his ex-Tiffany, after they successfully thwarted his murderous plot in Season One. While Jake and Devon encounter trouble as a couple at their new Catholic school, Chucky embarks on a whole new killing spree, crossing paths with familiar franchise faces along the way.